Analisis Akad Musyarakah sebagai Alternatif Pembiayaan Bebas Riba dalam Perspektif Maqashid Al-Syariah - Neti Haryani; Iksan Iksan; Muhammad Amin (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
This study aims to analyze the legal construction of the musyarakah contract as an alternative financing model free from riba, using the perspective of maqashid al-shariah in the practice of Islamic banking in Indonesia. As a contract based on the principles of partnership and profit-sharing, musyarakah is considered to best represent the identity of Islamic banking. However, in practice, its implementation often experiences a reduction in meaning, making it vulnerable to deviation from the primary objectives of Sharia. This study employs a normative legal research method through statutory, conceptual, and case approaches, by qualitatively examining primary, secondary, and tertiary legal materials. The findings show that the musyarakah contract has a strong legal foundation, namely Law Number 21 of 2008, DSN-MUI Fatwa Number 08/DSN-MUI/IV/2000, the Compilation of Sharia Economic Law, and several regulations issued by the Financial Services Authority. Nevertheless, substantively, its regulation still leaves room for improvement, particularly regarding clause standardization, risk distribution, and the function of Sharia supervision. The ideal formulation of this contract from the perspective of maqashid al-shariah requires affirming the position of the parties as partners, determining profit-sharing through a ratio, allocating losses proportionally, limiting the function of collateral, ensuring transparency, strengthening Sharia governance, and clarifying the dispute resolution mechanism. Accordingly, musyarakah can serve as a financing instrument that is genuinely free from riba, just, and capable of bringing benefits to all parties.